3D Printing In Novel Drug, Dosage Forms - Shaistha Khanam,; Shivani Chandra Jadhav,; Marikatti Parimala,; Kore Prabhakаr,; Nagula Jashwanth, (Asian Journal of Pharmaceutical Research and Development, 2026)
3D printing is a modern way of making things by adding materials layers by layer from digital designs. It is used in many areas like making automobiles, pharmaceutical industry. In medicines it helps create personalized drugs and medical devices, such as implant and different forms of medicine that fit individual needs. The first 3D printing was approved in ‘‘2015”. Which opened new possibilities for making complex medicines that release drugs in a controlled way and allow personal dosing. However, there are still challenges to solve, including technical problems and rules to follow before this technology can be widely used in healthcare. Once these challenges are met, 3D printing can help provide more personalized care for patients. This review explains the common 3D printing methods used in making medicines and medical devices, including examples of drugs made with this technology that are still being developed or are already available. Overall, 3D printing shows great potential to change how medicines and healthcare products are made by allowing for customization, faster production, and creating new types of treatments, improving healthcare for people.